Thematic Variation and Key Relationships: Charlotte's Theme in Max Steiner's Score for Now, Voyager - Leinberger, Charles (Journal of Film Music, 2009)
Austrian-born composer Max Steiner (1888-1971), who moved to Hollywood, California, in 1929, played an important role in bringing to American movies a musical style inspired by the works of late nineteenth-century romantic composers. Coming to Hollywood in the early days of sound film made him one of the first composers to combine the techniques of nineteenth-century German- Austrian composition with twentieth-century sound-film technology. Although this discussion will focus on many of the rhythmic and harmonic variations that Steiner uses, the author intends to demonstrate how these themes and their subsequent variations are used to create unity throughout the score.